QUALITY OF LIFE IN VITILIGO PATIENTS AT H. ADAM MALIK GENERAL HOSPITAL MEDAN, INDONESIA - Jusuf, Nelva Karmila; putra, imam budi; utami, dina rizki (Sumatera Medical Journal, 2017)
Background: Vitiligo is an acquired depigmenting skin disorder that can affect the patients’ quality of life (QOL).Objectives: The aim of this study was to evaluate the QOL in patients with vitiligo.Patients and Methods: This study included 30 patients with vitiligo. All the patients filled out questionnaires Skindex- 29. Data were compiled and analyzed statistically.Results: Among the 30 vitiligo patients, 73,3 % were women and 26,7 % were men. Mean age of patients were 40.53 ± 12. 91 years old. The mean duration of vitiligo was 9.07 ± 7.643 years. Themean total Skindex-29 score of the subjects was 24.68 ± 7,72. There was significant difference according to age’s group (p =0,035) and sex ( p = 0,01) but there is no significant difference according to duration of disease’s group ( p = 0,582 ).Conclusions: The study findings showed that vitiligo has a significant effect on the patients’ QOL. It seems counselling is needed as part of treatment in vitiligo patients.